Pengaruh Pemberian Air Rebusan Daun Seledri pada Lansia Penderita Hipertensi di Desa Bejangkar Kec.Batahan Kab. Madina Tahun 2022 - Ernawati Ernawati; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Julia Laia (PPNI UNIMMAN, 2024)
Hypertension, or high blood pressure, is a condition in which the pressure in the arteries increases. In general, this condition often does not cause symptoms, but blood pressure that is too high can increase the risk of stroke, aneurysm, heart failure, heart attack, and kidney damage. This study aims to analyze the effects of giving boiled celery water to elderly people with hypertension in Bintungan Bejangkar Village, Batahan District, Mandailing Natal Regency in 2022. This study is an experimental type with a one group pre-post test design. In this design, researchers use one group of subjects who will be observed before and after being given treatment. The study was conducted in Bintungan Bejangkar Village, Batahan District, Mandailing Natal Regency in 2022. The study population was 51 people, with a sample of 20 people selected using the Simple Random Sampling technique. The results of the study analyzed using the Wilcoxon test showed that the calculated Z value for systolic blood pressure was -2.911 with a p-value of 0.004. Based on these results, it can be concluded that giving boiled celery water has an effect on reducing blood pressure, both systolic and diastolic, in the elderly with hypertension in the Bintungan Bejangkar Village area, Batahan District, Mandailing Natal Regency in 2022.